Endothelial dysfunction in experimental models of metabolic syndrome − effect of fructose - Kaprinay B.; Gáspárová Z.; Lipták B.; Frimmel K.; Sotníková R. (Sciendo, 2017)
The aim of the work was to find an experimental model suitable for the study of endothelial dysfunction induced by MS. We used hypertriglyceridemic rats (HTG) that were fed a hypercholesterolemic diet of different composition and duration: a 6-week administration of standard diet with an addition of cholesterol and fat (HTGChol) and a three-month administration of the same diet with an addition of fructose (HTGCholF). We investigated the effect of different diets on aortic endothelial function. The standard diet fed Wistar (W) and HTG rats served as controls. Decision for addition of fructose to HTGChol was done based on in vitro experiments evaluating the effect of high concentration of saccharide in the incubation solution on aortic endothelial function. This intervention caused significant deterioration of relaxation induced by acetylcholine (ACh). While in HTGChol, we did not find significant differences in the function of the aorta compared to W or HTG rats, adding of fructose to high fat diet and prolonging its administration resulted in significantly impaired endothelium-dependent relaxation. It seems that such a model is suitable for the study of endothelial dysfunction in MS and the effect of substances that may protect the endothelium.